PENGARUH KONSENTRASI LARUTAN DAUN SELADA SEBAGAI PENGAWET ALAMI TERHADAP KUALITAS FISIKOMIAWI DAGING AYAM BROILER : The Effect Of Lettuce Leaf Solution Concentration As A Natural Preservative On The Physicomic Quality Of Broiler Chicken Meat - Mesrania Malo; Yessy Tamu Ina (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2026)
This research was conducted at the Integrated Laboratory of Wira Wacan Christian University, Sumba, with the aim of utilizing natural food ingredients in the form of lettuce leaves as an alternative preservative in broiler chicken meat. The study used a completely randomized design (CRD) consisting of 4 treatments with 5 replications. The treatments given were P1 with a concentration of 5%, P2 with a concentration of 8%, P3 with a concentration of 11%, and P4 with a concentration of 14%, resulting in a total of 20 experimental sample units. The observed variables included water content, pH, organoleptic tests (color, taste, texture, and preference level), and total proximate profile analysis. The research data were analyzed using analysis of variance (ANOVA) at a significance level of 5%. The results showed that: Treatment with a concentration of 14% (P4) showed the best results in color and taste parameters. Meanwhile, a concentration of 8% (P2) produced the highest value in terms of texture and panelists' preference level. In general, treatment with a concentration of 8% is considered the most optimal condition because it achieves the best level of panelist acceptance and is able to provide a balance in the product's sensory. The higher concentration of lettuce solution has a positive impact on the Proximate Profile, namely the meat protein content does not exceed the SNI standard, the meat fat is within the normal category, and the meat is preserved due to the low water content. The results of the study showed that the best water content value was 43,30%, pH was 5,26%, while the best organoleptic value in terms of color was 3,10%, taste was 2,80%, texture was 2,45%, and preference was 2,55%.